2021
DOI: 10.17984/adyuebd.719885
|View full text |Cite
|
Sign up to set email alerts
|

Fen Bilgisi Öğretmen Adaylarının “Enerji” Kavramına İlişkin Bilişsel Yapılarının ve Kavram Yanılgılarının Belirlenmesi

Abstract: The concept of "Energy", which is one of the concepts directly related to vital activities increases in importance day by day with the increasing technology and industrialization. For this reason, the concept of "Energy" learned in primary, secondary and higher education programs has a privileged place in science education as being an interdisciplinary concept. The aim of this study is to reveal the cognitive structures of pre-service science teachers about the concept of "Energy" and to determine their miscon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…She deduced from the students' expressions that most of them understand the explanations, but she noted that a few students who stayed silent and had confused looks could not assimilate it. In a similarly situation, Avcı et al (2012) found that many students mistakenly believe that "if an object moves, we are always doing work. "…”
Section: Students' Conceptions and Views About Force And Motionmentioning
confidence: 99%
“…She deduced from the students' expressions that most of them understand the explanations, but she noted that a few students who stayed silent and had confused looks could not assimilate it. In a similarly situation, Avcı et al (2012) found that many students mistakenly believe that "if an object moves, we are always doing work. "…”
Section: Students' Conceptions and Views About Force And Motionmentioning
confidence: 99%